Opportunities and Difficulties in the Repurposing of HDAC Inhibitors as Antiparasitic Agents - Tapas Kumar Mohapatra; Reena Rani Nayak; Ankit Ganeshpurkar; Prashant Tiwari; Dileep Kumar (MDPI AG, 2024)
Ongoing therapy for human parasite infections has a few known drugs but with serious side effects and the problem of drug resistance, impelling us to discover novel drug candidates with newer mechanisms of action. Universally, this has boosted the research in the design and development of novel medicinal agents as antiparasitic drugs with a novel mode of action. Histone deacetylase inhibitors (HDACis) are used in a vast variety of diseases due to their anti-inflammatory properties. Drug repurposing strategies have already approved HDACis as cancer therapeutics and are now under investigation for many parasitic infections. Along with the expression of the gene, histone deacetylase (HDAC) enzymes also act as a slice of great multi-subunit complexes, targeting many non-histones, changing systemic and cellular levels signaling, and producing different cell-based specified effects. Zinc (Zn2+)- and nicotinamide adenine dinucleotide (NAD+)-dependent HDACs of parasites play pivotal roles in the alteration of gene expression of parasites. Some of them are already known to be responsible for the survival of several parasites under odd circumstances; thus, targeting them for therapeutic interventions will be novel for potential antiparasitic targets. This point of view outlines the knowledge of both class-I and class-II HDACis and sirtuin inhibitors that emerged to be the key players in the treatment of human parasitic disorders like Leishmaniasis, Schistosomiasis, Malaria, Trypanosomiasis, and Toxoplasmosis. This review also focuses on repurposing opportunities and challenges in HDAC inhibitors that are preceded by their clinical development as potent new antiparasitic drugs.